Combining biomass wet disk milling and endoglucanase/β-glucosidase hydrolysis for the production of cellulose nanocrystals. (5th September 2015) - Teixeira, Ricardo Sposina Sobral; Silva, Ayla Sant'Ana da; Jang, Jae-Hyuk; Kim, Han-Woo; Ishikawa, Kazuhiko; Endo, Takashi; Lee, Seung-Hwan; Bon, Elba P.S.
Highlights: MFC and CNC were obtained from cellulose, holocellulose, pulp, and sugarcane. MFC was obtained via WDM and CNCs via WDM and enzymatic hydrolysis. WDM resulted in MFCs of 1000–5000 nm in length and 4–35 nm in diameter. Endoglucanases hydrolyzed MFCs into CNCs under mild reaction conditions. CNCs (500–1500 nm length; 4–12 nm diameter) with high aspect ratios were obtained. Abstract: Cellulose nanocrystals (CNCs), a biomaterial with high added value, were obtained from pure cellulose, Eucalyptus holocellulose, unbleached Kraft pulp, and sugarcane bagasse, by fibrillating these biomass substrates using wet disk milling (WDM) followed by enzymatic hydrolysis using endoglucanase/β-glucosidase. The hydrolysis experiments were conducted using the commercial enzyme Optimash™BG or a blend of Pyrococcus horikoshii endoglucanase and Pyrococcus furiosus β-glucosidase. The fibrillated materials and CNCs were analyzed by X-ray diffraction, atomic force microscopy, scanning electron microscopy, and the specific surface area (SSA) was measured. WDM resulted in the formation of long and twisted microfibers of 1000–5000 nm in length and 4–35 nm in diameter, which were hydrolyzed into shorter and straighter CNCs of 500–1500 nm in length and 4–12 nm in diameter, with high cellulose crystallinity. Therefore, the CNC's aspect ratio was successfully adjusted by endoglucanases under mild reaction conditions, relative to the reported acidic hydrolysis method.